A Study on Students\' Lived Experiences of Hijab Limitations in Islam - F. Karimi; B. Talebi, Ph.D. (خانواده و پژوهش, 2021)
Increasing women’s self-concept and positive perception of hijab are among the most priority strategies used to internalize the value of hijab. Strengthening the religious spirit to adhere to social values, broadening women’s knowledge about genuine Islamic values, and taking the subject of chastity and hijab scientifically into account are helpful in enhancing the culture of chastity. The present research is an endeavor to examine students’ perception of the limits of the hijab in Islam while examining their lived experiences. This study is based on a qualitative and phenomenological approach. Purposeful sampling method was utilized and ten respondents were selected from among female eleventh graders in Tabriz. Twelve individual interviews and a semi-structured group interview were carried out. The students were interviewed outside schools so that the school climate would not affect their perception of hijab. Data analysis was undertaken based on the seven-stage Colaizzi's method. The findings showed that according to the students’ lived experiences, hijab is not only limited to clothing but it also includes chastity and hijab in look, speech, behavior, and clothing. The extracted themes based on students’ lived experiences were as follows: different interpretations of limitations of hijab, the impact of individuals’ past experiences on limitations of hijab, the dependence of limitations of hijab on the environment, limitations of hijab as a function of time, the impact of the virtual world on hijab’s fading away, weak faith as the reason for having intermittent perspective on hijab.